An assessment on cinematic composition, narrative structure and semiotics in animated films: a case study of Filem Negara Malaysia’s anthropomorphic animal folktales (Sang Kancil: the animated series) / Azahar Harun - Harun, Azahar (Institute of Graduate Studies, UiTM, 2013)
This study concerns the anthropomorphic animal folktale namely Sang Kancil: The Animated Series (SKTAS) produced by Filem Negara Malaysia (National Film Department) during the late 1970s and early 1980s. These animated series are Hikayat Sang Kancil (Xavier, A, 1978); Sang Kancil & Monyet, (Hassan Abd Muthalib, 1984); and Sang Kancil & Buaya (Hassan Abd Muthalib, 1987). In general, the study comprises of two parts, Historical Perspective and Analytical Perspective. In the first part, the study attempts to establish insight regarding the historical background of the agency. Here it identifies some of the important historical events which are crucial for the development of animation production in this country. These events are found in three major periods, Colonial (1949-1956), Post-Colonial (1957-1960), Contemporary (1970- 2000). Among the topics discussed in this section, includes the establishment of the Malayan Film Unit and Film Negara Malaysia, the contribution made by animation pioneers and the review of anthropomorphic animal folktale from 1970 to 2000. In the second part, the study looks at the construction of Sang Kancil: The Animated Series (SKTAS) by analyzing three important aspects, Cinematic Composition, Narrative Structure and Semiotics. Here, it poses the question of what formula did the artist employ to construct the animated series (SKTAS). In context of cinematic, a mix method (qualitative & quantitative) was explored which include a Shot-by-shot analysis and a Statistical Style Analysis (Salt, 1974). This approach aims to establish baseline information regarding the cinematic convention (Duration, Setting and Camera Technique). In context of Narrative, a method called Freytag‘s Pyramid Analysis (Freytag, 1893 cited in Griffith, 2011) was employed. This approach enables the researcher to analyze the narrative structure of the samples thus determining its characteristics (Exposition, Rising Action, Climax, Falling Action and Resolution). In context of Semiotics, the study attempts to identify the symbolism element called ‗Signifier and Signified‘ (Saussure, 1966 cited in Berger, 1992) and interpreting its meaning in relation to Malaysian history, politics and culture. The study concludes with a summary of the findings from the earlier chapters (Chapter Four, Chapter Five & Chapter Six).